A 2.4-GHz ISM RF and UWB hybrid RFID real-time locating system for industrial enterprise Internet of Things. Issue 6 (3rd July 2017) - Zhai, Chuanying; Zou, Zhuo; Zhou, Qin; Mao, Jia; Chen, Qiang; Tenhunen, Hannu; Zheng, Lirong; Xu, Lida
ABSTRACT: This paper presents a 2.4-GHz radio frequency (RF) and ultra-wide bandwidth (UWB) hybrid real-time locating system (RTLS) for industrial enterprise Internet of Things (IoT). It employs asymmetric wireless link, that is, UWB radio is utilised for accurate positioning up to 10 cm in critical sites, whereas 2.4-GHz RF is used for tag control and coarse positioning in non-critical sites. The specified communication protocol and the adaptive tag synchronisation rate ensure reliable and deterministic access with a scalable system capacity and avoid unpredictable latency and additional energy consumption of retransmissions due to collisions. The tag, consisting of a commercial 2.4-GHz transceiver and a customised application-specific integrated circuit (ASIC) UWB transmitter (Tx), is able to achieve up to 3 years' battery life at 1600 tags per position update second with 1000 mAh battery in one cluster. The time difference of arrival (TDoA)–based positioning experiment at UWB radio is performed on the designed software-defined radio (SDR) platform.